2017
DOI: 10.1053/j.ajkd.2016.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Estimated GFR Before and After Bariatric Surgery in CKD

Abstract: Background: Several reviews have recently detailed the beneficial effects of weight loss surgery for kidney function. However, these studies have a number of limitations, including small sample size, few done in chronic kidney disease (CKD) stages 3 and 4, and many not including the main bariatric surgery procedures used in the United States today. Study Design: This was an observational retrospective cohort study comparing propensity score–matched bariatric surgery patients and nonsurgery control patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
51
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(62 citation statements)
references
References 41 publications
6
51
0
5
Order By: Relevance
“…Bariatric surgery increased eGFR in obese patients with CKD [28]. In a previous study, although improvement of eGFR was greater by Roux-en-Y gastric bypass than LSG, eGFR increased from 48.5 to >60 mL/min/1.73 m 2 1 year after LSG [28]. Our study also showed significant improvement of eGFR 1 year after LSG.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Bariatric surgery increased eGFR in obese patients with CKD [28]. In a previous study, although improvement of eGFR was greater by Roux-en-Y gastric bypass than LSG, eGFR increased from 48.5 to >60 mL/min/1.73 m 2 1 year after LSG [28]. Our study also showed significant improvement of eGFR 1 year after LSG.…”
Section: Discussionsupporting
confidence: 67%
“…Increased tumor necrosis factor-α (TNF-α) and monocyte chemotactic protein-1 (MCP-1) as well as ectopic lipid accumulation in the kidney were regarded as important mechanisms of ORG [26, 27]. Bariatric surgery increased eGFR in obese patients with CKD [28]. In a previous study, although improvement of eGFR was greater by Roux-en-Y gastric bypass than LSG, eGFR increased from 48.5 to >60 mL/min/1.73 m 2 1 year after LSG [28].…”
Section: Discussionmentioning
confidence: 99%
“…The literature suggests that the use of markers that suffer less interference due to loss of muscle mass, such as cystatin C, may be a better and more reliable alternative for estimating renal function in patients who lose weight sharply, especially when at the same time uses cystatin C and creatinine by CKD Epi, based on this evidence the analysis of the present study [27,34,37].…”
Section: Discussionmentioning
confidence: 61%
“…Studies have pointed the improvement of renal function after bariatric surgery, either with increased glomerular iltration rate in patients with chronic kidney disease [37], or reduction of hyper iltration in patients with no evidence of kidney disease [15,16,19]. However, in some studies the sample is too small and in others the biomarkers presents low sensitivity [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…With regard to metabolic surgery, several recent observational studies report that it is associated with improvements in albuminuria, eGFR, and prognostic risk for CKD (5)(6)(7)(8). Two of these studies also reported slower progression to a composite end point of ESKD and stage 5 CKD or doubling of serum creatinine (5,7).…”
Section: Intentional Weight Reduction and Protection Against Kidney Dmentioning
confidence: 99%